Activation of the Immune Coagulation System by Murine Hepatitis Virus Strain 3 - Levy, G. (Rev Infect Dis, 1989)
Viral infections result in alterations in hemostasis and coagulation. It has previously been shown that susceptibility to murine hepatitis virus strain 3 (MHV-3), a coronavirus, correlates directly with the spontaneous, T lymphocyte-instructed expression of a procoagulant monokine that exhibits prothrombin-cleaving activity (procoagulant activity [PCA]). A biologic role for PCA in the pathogenesis of MHV-3 infection is suggested by results of in vivo microscopic observations made during acute MHV-3 infection. Recently, it has been demonstrated that prostaglandin E2 abrogates the induction of PCA by MHV-3 both in vivo and in vitro and prevents hepatic necrosis and the associated microcirculatory changes. These data suggest that MHV-3 induces cellular injury through the activation of the coagulation cascade and provide further evidence for a role for PCA in the pathogenesis of MHV-3 infection.